2021
DOI: 10.1002/jpen.2074
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Evidence of Treatment, Tolerance, Healthcare Utilization, and Costs Among Postacute Care Adult Patients Receiving Enteral Peptide‐Based Diets in the United States

Abstract: Objective: Peptide -based (PB) enteral tube feeding (ETF) formulas have been shown to reduce gastrointestinal (GI) intolerance in patients receiving enteral nutrition. However, limited data exist in relation to their use in the postacute/home care setting. We sought to assess the real-world GI tolerance, healthcare utilization, and resource use costs of 100% whey-protein PB ETF in adults in a postacute care setting and describe their demographic, clinical, and treatment characteristics.Method: Using medical cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…A review of >1000 insurance claims for patients who received EN has found that transition to PBD in home‐care adults previously receiving oral and enteral SPF reduced hospitalizations and overall cost of care. 14 LaValle et al noted a significant increment ( P < .001) in EN tolerance by 18% with transition to PBD over 1 year. Moreover, a 28% reduction in at least one hospitalization over a period of 1 year was found in those who transitioned to 100% whey protein PBD.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A review of >1000 insurance claims for patients who received EN has found that transition to PBD in home‐care adults previously receiving oral and enteral SPF reduced hospitalizations and overall cost of care. 14 LaValle et al noted a significant increment ( P < .001) in EN tolerance by 18% with transition to PBD over 1 year. Moreover, a 28% reduction in at least one hospitalization over a period of 1 year was found in those who transitioned to 100% whey protein PBD.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, healthcare utilization related to EFI can be significant and lead to a higher cost of care and/or overwhelming nutrition care for patients and caregivers. A review of >1000 insurance claims for patients who received EN has found that transition to PBD in home‐care adults previously receiving oral and enteral SPF reduced hospitalizations and overall cost of care 14 . LaValle et al noted a significant increment ( P < .001) in EN tolerance by 18% with transition to PBD over 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations